40‐3: High Light Efficiency LCD using Flip Panel Structure. Issue 1 (28th June 2021) - Hirai, Akira; Hasegawa, Masahiro; Nakai, Takako; Kawahira, Yuichi; Sakai, Akira; Shimada, Shinji; Minoura, Kiyoshi
Abstract : A novel LCD using a flip panel structure has been developed to improve light utilization efficiency of LCD modules. By combining a flip panel structure and a CF substrate with an aluminum matrix on the backlight side, a 13‐inch flip panel prototype has successfully demonstrated 1.22 times higher efficiency than a conventional non‐flip panel. The flip structure could make the LCD modules fully flat and light‐weighted by removing cover glasses.